2012
DOI: 10.1186/alzrt110
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of low-density lipoprotein receptor-related protein (LRP1) in hippocampal neurons does not proportionately reduce, or otherwise alter, amyloid deposition in APPswe/PS1dE9 transgenic mice

Abstract: IntroductionThe low-density lipoprotein receptor-related protein (LRP1) and its family members have been implicated in the pathogenesis of Alzheimer's disease. Multiple susceptibility factors converge to metabolic pathways that involve LRP1, including modulation of the processing of amyloid precursor protein (APP) and the clearance of Aβ peptide.MethodsWe used the Cre-lox system to lower LRP1 levels in hippocampal neurons of mice that develop Alzheimer-type amyloid by crosses between mice that express Cre reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
(50 reference statements)
5
9
0
Order By: Relevance
“…This presumption is supported by the presence of only mature fibrillary plaques, without new inflammatory plaques, in the hippocampus of 24-month-old APP/PS1 mice. Similar to adult APP/PS1 mice, the deposition of Aβ plaques was mainly present in the molecular layer and stratum lacunosum moleculare, while being virtually absent in the pyramidal cell layer and the granule cell layer (Bas Orth et al 2005;Oksman et al 2006;Donkin et al 2010;Scott et al 2012;Xu et al 2012Xu et al , 2016. Furthermore, our previous and present results suggest that laminar heterogeneity and Aβ load is correlated with laminar variability in expression of APP secretases (Xu et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…This presumption is supported by the presence of only mature fibrillary plaques, without new inflammatory plaques, in the hippocampus of 24-month-old APP/PS1 mice. Similar to adult APP/PS1 mice, the deposition of Aβ plaques was mainly present in the molecular layer and stratum lacunosum moleculare, while being virtually absent in the pyramidal cell layer and the granule cell layer (Bas Orth et al 2005;Oksman et al 2006;Donkin et al 2010;Scott et al 2012;Xu et al 2012Xu et al , 2016. Furthermore, our previous and present results suggest that laminar heterogeneity and Aβ load is correlated with laminar variability in expression of APP secretases (Xu et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…It has been observed that in this strain of transgenic mice, there is considerable variability in the Ab load within the individual younger animals (6 to 7 months) that will tend to normalize as the animals age (10). Plaque numbers within the animals used in this study were similar to those previously reported for this strain (10).…”
supporting
confidence: 77%
“…Plaque numbers within the animals used in this study were similar to those previously reported for this strain (10). Although this is the identical strain and group sizes used by Cramer et al (1), our experience with this strain suggests that larger group sizes may be needed to detect small reductions in amyloid load.…”
supporting
confidence: 70%
“…In contrast, 5 and 10 weeks of SSR240612 treatment significantly increased (approximately 30 to 40%) LRP-1-labeled area and intensity in APP mice depending on the brain region (Figure 6A). Neuronal LRP-1, in contrast, remained unchanged after treatment, compatible with neuronal LRP-1 expression being independent of amyloidosis in AD mice [39]. As MMP9 is involved in both BBB integrity and Aβ clearance [40-43], its protein levels were also measured.…”
Section: Resultsmentioning
confidence: 98%